ANALISIS STRATEGI PERSAINGAN BANK PERKREDITAN RAKYAT (BPR) DALAM PASAR KREDIT MIKRO DAN KECIL DI EKS-KARESIDENAN BESUKI TAHUN 2011 (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2011)
Community Bank have characteristics to serve small or local customers and tend to serve retail loans than corporate loans and use relationship and qualitative data in micro and smal credit market. This research aims to determine market competition strategy of Community Bank in micro and small credit in Eks-Karesidenan Besuki. This research using primary data from key-informant with snowball method. Data was collected by questionnaire and indept interview. Research analysis method using the Analysis Hierarchy Process (AHP). The results showed the Community Bank have a dominant strategy in the institutional aspects and marketing in micro and small credit market. Institutional Community Bank strategy use a network of colleagues and management partners. Community Bank implemented marketing strategies with all segments, the promotion, marketing approaches using capacity to culture and language of the prospective loan customers.